THE EFFECT OF ATTITUDE TOWARDS EMOTIONAL EXPRESSION ON SOCIAL ANXIETY IN SOCIAL MEDIA AND ITS RELATIONSHIP WITH COPING STYLES - Herng, Loo Huan (International Journal of Psychosocial Rehabilitation, 2020)
Social anxiety in social media was related to the anxiety formed due to the fear and uneasiness towards social interactions in a social media setting. A person’s attitude towards emotional expression was a factor that is related to social anxiety in social media. Positive attitude towards emotional expression can reduce the social anxiety in social media whereas negative attitude can worsen the social anxiety in social media. Effective coping style can be used to reduce the level of social anxiety in social media. The research objective was to investigate the effect of the attitude towards emotional expression on the level of social anxiety in social media among university students. This research also aimed to investigate the relationship between coping styles and social anxiety in social media. A total of 210 public university students of Psychology Program involved in this quantitative research. The data obtained was analysed through correlation test and simple regression test. Research result show that there was attitude of emotional expression predicted the level of social anxiety in social media among university students. In addition, this research also found that denial, behavioural disengagement and self-blame coping style is positively correlated with social anxiety in social media. Therefore, avoidance in using of these coping styles may aid in reducing the social anxiety in social media.